2020
DOI: 10.1371/journal.pone.0239805
|View full text |Cite
|
Sign up to set email alerts
|

Institutional environments and breakthroughs in science. Comparison of France, Germany, the United Kingdom, and the United States

Abstract: Scientific and/or technical breakthroughs require the exploration of novel ideas and technologies. Yet, it has not been studied quantitatively how national institutional contexts either facilitate or stifle organizational support for exploration. Available qualitative evidence suggests that institutional contexts that exert weak control over universities and research organizations strengthen their capabilities to achieve scientific breakthroughs, while contexts with strong control constrain them. The paper is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…This result corroborates findings from Stephan and Levin (2001). At the same time, the United States has become more specialized in the later career phases (PWR, NP), indicating its growing attractiveness over the twentieth century as a work environment for future laureates (Heinze et al, 2020). These developments are especially pronounced in the medical sciences.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This result corroborates findings from Stephan and Levin (2001). At the same time, the United States has become more specialized in the later career phases (PWR, NP), indicating its growing attractiveness over the twentieth century as a work environment for future laureates (Heinze et al, 2020). These developments are especially pronounced in the medical sciences.…”
Section: Resultsmentioning
confidence: 99%
“…(1) the university where future Nobel laureates received their highest academic degree (HD), (2) the university or research organization where they performed their prize-winning research (PWR), and (3) the university or research organization where they were employed at the time of the award (NP). Our analysis covers 100 years of an existing dataset (Heinze et al, 2020;Heinze et al, 2019a, b) that includes the entire time period 1901-2020 (120 years). The primary data source was the Nobel Foundation's website (www.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Flexibility can provide backup or recovery plans when problems emerge in a planned task. This is especially possible when the environmental conditions allow sufficient freedom and flexibility to the scientists (Heinze 2008;Heinze et al 2020;Hollingsworth 2004). For example, when the IceCube team found that bubble-free ice did not exist until a considerably greater depth than they had initially thought, they realized they had a problem.…”
Section: Sources Of Uncertainty In Sciencementioning
confidence: 99%
“…Some scholars note that the rewards to undertaking risky research are only descernable with a long delay ( Wang, Veugelers, and Stephan 2017) and are modest compared to those for incremental research (Foster, Rzhetsky, and Evans 2015). Some emphasize the role played by the institutional environment (Hollingsworth 2004), suggesting that risk-taking is disfavored by systems that exert strong control on universities and research institutions (Heinze, von der Heyden, and Pithan 2020), and that the increase in competitive funding, and short-term positions reduces the ability and willingness of scientists to conduct risky research (Laudel 2017;Wang, Lee, and Walsh 2018).…”
Section: Introductionmentioning
confidence: 99%